Geothermal Conditions and Mesozoic-Cainozoic Evolution of the Carpatho-Pannonian Region - R. I. Kutas (Геофизический журнал, 2016)
This paper presents new two-dimensional (2D) numerical geothermal models of the lithosphere and the results of their geodynamic analysis together with the crustal structure models along three deep seismic sounding profiles crossing the Western and Eastern Carpathians from the Pannonian basin to the Paleozoic West European and the Precambrian East European Platforms. The construction and interpretation of the geothermal 2D models are based on the numerical solution of both the steady state and transient heat conduction equations. The obtained geophysical and geothermal models demonstrate the significant variations in the lithosphere thickness, crustal layering, temperatures and seismic velocities distribution. Taking into consideration the crustal structure and heat flow distribution, all cross-sections can be divided into three sectors with different age of the crust: Neoalpine, Mesozoic—Late Paleozoic, early Paleozoic—Late Proterozoic. The boundaries between sectors mismatch a tectonic zonation of the upper crust. The heat flow density reaches 80—130 mW/m2 in the Pannonian basin and Transcarpathian trough (areas of Neoalpine tectonic activity). It decreases to 60—70 mW/m2 in the Inner Carpathians, inner part of the Outer Carpathians and on the West European platform (areas of Mesozoic—Late Paleozoic activity), and to 35—60 mW/m2 in the most of the Outer Carpathians, in Carpathian foredeep, Trans European suture zone, as well as the East European margin (areas of early Paleozoic—Late Proterozoic activity). The decrease in heat flow is accompanied with an increase in the lithosphere and crust thickness. The geothermal lithosphere thickness varies from 65—80 km beneath the Pannonian basin to 120—150 km beneath the Inner Carpathians and the Paleozoic platform, and to 180—200 km beneath the East European platform, and the depth of Moho discontinuity changes from 22—30 km to 30—40 km and 40—50 km accordingly. The high heat flow in the Pannonian basin is of a mantle origin. It is caused by the Miocene extension and lithosphere thinning, formation of fault and rift systems, the asthenospheric upwelling due to the subduction of the oceanic lithosphere in the time interval from late Cretaceous to Paleogene. The current structure of the Carpathian-Pannonian region was formed as a result of Neogene continental collision between the European plate and the Alcapa and Tisza microplates. Being developed in a compressional stress regime, the collision process was accompanied by lateral relative movements of the microplates along the shear zones, the upper Alcapa crust obducting over the Pennine tectonic unit or the platform margins, and underthrusting of the Pannonian lower crust and the uppermost mantle beneath the lithosphere of the European plate.